Edukacja medialna ucznia w szkole podstawowej = Media education in the elementary school - Nowicka, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Media education in a world dominated by the media is an extremely important part of education at school. Media education practiced already in preschool age and continued in early childhood education is an opportunity to prepare children to critically understand how media communicates and use it as a tool for self-development.
Keywords: media; multimedia; technologie informacyjne; edukacja medialna; wychowanie; rodzina; szkoła; dziecko; information technology; media education; education; family; school; child